Kesejahteraan Material Warga Emas Desa: Data Mikro daripada Daerah Limbongan, Kelantan (Jurnal Pembangunan Sosial, 2015)
While research on material well-being of older persons has been well established in developed countries, research of material well-being among this category of population is still relatively not well established in Malaysia. Economic-wise the older people are more vulnerable than of the younger ones. The objectives of this study are to analyse the level of material well-being of rural older persons, and to identify the extend to which their material well- being is being influenced by their human and social capitals. To achieve these objectives, data from 214 people aged 60 years and above in rural Kelantan were collected. From the survey, 14 demographic and social variables were analysed to determine their influence on the material well-being of the older persons. On a whole, it was found the level of material well-being of the majority of the respondents is quite low. Results also showed that education, working experiences, the number of children and housing quality are variables that have a significant influence on the material well-being of the rural older persons.